Call for action: addressing the alarming surge of HIV in Madagascar - Andrianarimanana-Köcher, Diavolana; Rakotoarivelo, Rivo Andry; Randria, Mamy Jean de Dieu; Raberahona, Mihaja; Ratefiharimanana, Andosoa; Andriamasy, Emmanuel Harizaka; Vallès, Xavier; Benski, Anne-Caroline; Emmrich, Julius; Walsh, Andrew; Robinson, Kyle; Muller, Nadine (BMJ global health, 2024)
Summary box - - In stark contrast to its neighbours in Sub-Saharan Africa, Madagascar reports an estimated HIV prevalence below 0.5%.1 HIV infections are perceived to be primarily concentrated in key populations. However, closer inspection suggests an underestimated epidemic transitioning to the general population. - - A 2020 analysis by Raberahona et al on the status of HIV in Madagascar already suggested that the country may be on the verge of a high-prevalence epidemic, with a concerning …
Gesehen am 10.10.2024